Growth Enhancement of Phragmites australis, Eichhornia crassipes and Saccharum officinarum for Rhizoremediation of Crude Oil - Ubogu, Monday; Odokuma, Lucky O.; Akponah, Ejiro (International Journal of Environment, 2018)
P. australis, E. crassipes (in mangrove swamp) and S. officinarum (in rainforest) are capable of tolerating some levels of crude oil in soil. However, some important growth characteristics such speedy growths, extensive root system and increased biomass desirable for efficient rhizoremediation are depressed. To cushion this suppressive effects, plants were subjected to the following treatments: Plant + Soil (PS) (Control); Plant + Soil + Oil (PSO); Plant + Soil + Oil + Fertilizer (PSOF); Plant +Soil + Oil + Fertilizer + Microorganisms (PSOFM); and Plant + Soil + Fertilizer + Microorganisms + Solarization (PSOFMS). Treatments were monitored for 120 days to determine their effects on the following growth parameters: Germination, germination percentage, height, and root length, dry weight, and leaf area. Results indicated that treatments PSOF, PSOFM and PSOFMS enhanced all growth parameters over contaminated untreated soil (PSO) with the exception of germination in P. australis and S. officinarum; while root length, leaf area in E. crassipes were statistically the same for PS, PSO, PSOFM and PSOFMS (P ˂ 0.05). Overall, growth enhancement efficiencies of the applied treatments were in the order: PSOFM ˃ PSOF ˃ PSOFMS. Thus, growth of these plants can be enhanced in crude oil contaminated soil by the above treatments for efficient rhizoremediation.